Women's Language Features Found In "The Help" Movie - Suciani Dewi, Ida Ayu Putu; Rajeg, Gede Primahadi Wijaya; Sri Rahayuni, Ni Ketut (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This study investigates the features, functions and differences of women’s language styles used by female characters of different skin colors in “The Help” movie. The movie was chosen because it involves many female characters and conversations among women of different races which are related to the purpose of this study. The data was collected by using documentation techniques and analyzed using qualitative methods based on the theory from Lakoff (1975) about women’s language; the formal method is used to present the analysis. The result shows there are 23 utterances identified with a total of six of women's language features used by women's characters, namely empty adjective, super polite form, lexical hedges, intensifier, tag question and hypercorrect grammar. Two categories of functions in the features of women's language are found in this study, that is weakening and strengthening the function. However, the most used features that are useful as weakening the function of the speech, namely lexical hedges, tag questions, super polite form, and hypercorrect grammar. There are several differences in the language styles of women characters of different races in this study, such as the differences in the frequency and the features used in women’s language. Keywords: Women’s Language, Women’s Language Features, Lakoff